Trichogramma cacoeciae as a biological control agent of the tomato pinworm Tuta absoluta in Northeastern Tunisia - Cherif, Asma; Kaouthar, Lebdi Grissa (ENTOMOLOGIA HELLENICA, 2013)
Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is considered as key pest attacking tomato in Tunisia and in many other countries around the world. In order to investigate the efficacy of Trichogramma cacoeciae (Marchal) (Hymenoptera: Trichogrammatidae) for biological control of this pest in Northeastern Tunisia, releases were performed in open field conditions. T. cacoeciae showed a good efficacy on reducing the number of T. absoluta eggs and larvae when releasing 30 adults/plant in plots covered with insect-proof netting in May 2012. The results showed that this parasitoid may be a promising agent for T. absoluta biological control in Tunisia.